Antiamoebic Activity of Marine Sponge Spongia officinalis var. ceylonensis Dendy (Bangladesh Pharmaceutical Journal, 2015)
Human amoebiasis due to infection by Entamoeba histolytica is mainly associated with morbidity thus affecting the quality of life and pace of developmental activities of countries with warm climatic conditions. A consistently high global incidence of this disease has been reported. In an endeavor to identify novel molecules with potent antiamoebic activity and lower side-effect, the present study was designed to investigate antiamoebic activity in Spongia officinalis extracts/fractions followed by isolation and characterization of bioactive molecules. The methanol extract of the S. officinalis showed promising in vitro and in vivo antiamoebic activity. On further fractionation, the activity was localized in the n-butanol soluble fraction from which the major purified fraction was identified as a mixture of alkaloids (xestospongins and araguspongins) by LCMS studies of the n-butanol soluble fraction DOI: http://dx.doi.org/10.3329/bpj.v17i1.22312 Bangladesh Pharmaceutical Journal 17(1): 38-42, 2014